2009
DOI: 10.1186/1477-7525-7-72
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of Health Related Quality of life of parents of chronically ill children: the importance of care-dependency of their child and their support system

Abstract: Background: Parents of chronically ill children are at risk for a lower Health Related Quality of Life (HRQoL). Insight in the dynamics of factors influencing parental HRQoL is necessary for development of interventions. Aim of the present study was to explore the influence of demographic and disease related factors on parental HRQoL, mediated by employment, income, leisure time, holiday and emotional support in a comprehensive model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 35 publications
(47 reference statements)
3
59
1
4
Order By: Relevance
“…This is in concordance with previous study in Lebanon using SF-36 (Sabbah et al, 2003). Prior research has shown that the family members influence each other mutually (Hatzmann et al, 2009;Panepinto et al, 2009;Duhamel, 2007), therefore, the family with children who have a chronic disease may have greater family burden, and need social support (Hatzmann et al, 2009;Panepinto et al, 2009). As has been reported in several studies (Dean et al, 2010;Abdel Hai, Taher, & Fattah, 2010;Farnik et al, 2010), it is well established that children with chronic conditions have significant impairments in HRQoL.…”
Section: Cancer Childsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in concordance with previous study in Lebanon using SF-36 (Sabbah et al, 2003). Prior research has shown that the family members influence each other mutually (Hatzmann et al, 2009;Panepinto et al, 2009;Duhamel, 2007), therefore, the family with children who have a chronic disease may have greater family burden, and need social support (Hatzmann et al, 2009;Panepinto et al, 2009). As has been reported in several studies (Dean et al, 2010;Abdel Hai, Taher, & Fattah, 2010;Farnik et al, 2010), it is well established that children with chronic conditions have significant impairments in HRQoL.…”
Section: Cancer Childsupporting
confidence: 89%
“…International studies on HRQOL in children are needed to gain a better understanding of the impact of public policies, interventions, therapies (Schmidt, Wenninger, Niemann, Wahn, & Staab, 2009), evaluation of interventions, and the prediction of health and social care need (Sabbah et al, 2003;Hatzmann, Maurice-Stam, Heymans, & Grootenhuis, 2009;Panepinto, Hoffmann, & Pajewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ha et al (25) suggested the detrimental impact on mental health of parents is reduced when parents had more positive support from family members. Other studies also reported that more emotional support was related with better cognitive and social functioning (26) and health-related quality of life of the parents (14). When under stress, an individual might turn to religion for many reasons as religion serves as a source of emotional support, a vehicle for positive reinterpretation and growth, or a tactic of active coping with a stressor (18).…”
Section: Discussionmentioning
confidence: 99%
“…Care dependency was defined as the number of life domains on which their child needs care (eight items-physical, mobility, eating and drinking, medication use, coping with devices/ tools, entertaining, contact with other children, education). This scale ranges from 0 to 8, where 0 indicates that the child does not need support at all, and score 8 indicates that the child needs full support (14). The pilot study showed that this scale had good internal consistency reliability with Cronbach's alpha = 0.86.…”
Section: Background Information Sheetmentioning
confidence: 99%
“…A single score is attributed to each combination. Scores of each subscale are normalized to a scale ranging from 0 to 100, with higher scores indicating better health and functioning (Hatzmann, Maurice-Stam, Heymanus & Grootenhuis, 2008).…”
Section: Family Healthmentioning
confidence: 99%